Analysis of luminescence method applicability for determination of Cd₁₋xZnxTe composition - Glinchuk, K.D.; Litovchenko, N.M.; Strilchuk, O.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Physical fundamentals are analyzed for the method of determination of Cd₁₋xZnxTe composition x from measurements of the luminescence band peak position, emission being caused by annihilation of bound exciton - shallow neutral acceptor complexes at 4.2 K. Found are the conditions when application of the method discussed enables to obtain reliable x values.